Answer:
See explanation below.
Step-by-step explanation:
From the definition of adjacent angles, the sum of measure of all the adjacent angles on a horizontal line equals to
.
From the given figure, we have:
![m\angle NPM+m\angle MPL+m\angle LPK\:=\:180^(\circ )\\\\m\angle NPM+63^(\circ )+90^(\circ )\:=\:180^(\circ )\\\\m\angle NPM\:=\:27^(\circ )\\](https://img.qammunity.org/2021/formulas/health/middle-school/txit7fnavvfux6trj61a1bamlwmilkzxqy.png)
And from the definition of alternate angles, we have:
![m\angle NPM\:=m\angle KPJ\:=\:27^(\circ )](https://img.qammunity.org/2021/formulas/health/middle-school/ohggeqpkqlehcmf4ajbuomea4nlw9gqm1j.png)